A Henoch-Schönlein Purpura Case with Clinical Manifestation of Gastrointestinal Bleeding: A Case Report - Dian Daniella; Pande Ketut Kurniari; Gde Somayana (HM Publisher, 2023)
Background: Henoch-schӧnlein purpura (HSP) or also known as immunoglobulin A (IgA) vasculitis, is an autoimmune vasculitis of small blood vessels. The incidence of HSP in adults is only 5 in 100,000 adult patients. One of the causes of these low incidences is due to misdiagnosed or underdiagnosed. This is inevitable as in adults, and the disease usually presents with atypical signs and symptoms. One of the rare manifestations of this disease is gastrointestinal tract bleeding. This study aimed to describe a case of Henoch-schӧnlein purpura with gastrointestinal bleeding and the treatment. Case presentation: A rare case of a 20-year-old adult male diagnosed with HSP with the chief complaint of severe abdominal pain and gastrointestinal bleeding was presented. The patient also complained of arthralgia. Upon closer examination, the patient had palpable purpura on both the ankle and trunk. Urinalysis showed protein (+2) with erythrocyte 25-50 cells. Esophagogastroduodenoscopy showed erosive pangastritis, bile reflux, and duodenal submucosal bleeding with a normal duodenal bulb. The patient was diagnosed with HSP and was given methylprednisolone and azathioprine. On 1 month follow-up, the patient's complaints subside. Conclusion: Henoch-schӧnlein purpura should be considered in adult patients, especially in patients with skin lesions without thrombocytopenia accompanied by multiorgan involvement (gastrointestinal, renal, and joint).